Patching gaps in plant genomes results in gene movement and erosion of colinearity - Wicker, Thomas; Buchmann, Jan P.; Keller, Beat

(untitled) (Genome Research, 2010)
Colinearity of genes in plant genomes generally decreases with increasing evolutionary distance while the actual number of genes remains more or less constant. To characterize the molecular mechanisms of this “gene movement,” we identified non-colinear genes by three-way comparison of the genomes of Brachypodium, rice, and sorghum. We found that genomic fragments of up to 50 kb containing the non-colinear genes are duplicated to acceptor sites elsewhere in the genome. Apparent movement of genes may usually be the result of subsequent deletions of genes in the donor region. Often, the duplicated fragments are precisely bordered by transposable elements (TEs) at the acceptor site. Highly diagnostic sequence motifs at these borders strongly suggest that these gene movements were the result of double-strand break (DSB) repair through synthesis-dependent strand annealing. In these cases, a copy of the foreign DNA fragment is used as filler DNA to repair the DSB linked with the transposition of TEs. Interestingly, most TEs we found associated with gene movement have a very low copy number in the genome and for several we did not find autonomous copies. This suggests that some of these elements spontaneously arose from unspecific interaction with TE proteins that are encoded by autonomous elements. Additionally, we found evidence that gene movements can also be caused when DSBs are repaired after template slippage or unequal crossing-over events. The observed frequency of gene movements can explain the erosion of gene colinearity between plant genomes during evolution.